Purchase Decisions For Thrift Online Stores (Case Study On Students Science Education FMIPA UNM Makassar) - Andi Ainun Abdillah; Hasnawi Haris; Aslinda; Risma Niswaty; Andi Muhammad Rivai (Fakultas Ilmu Sosial dan Hukum, 2025)
The study aims to find out how the decision to purchase thrift online store for Science Education Students Makassar State University Batch 2021. The study uses qualitative research methods. Data collection techniques used are through observation, interviews, and documentation. The number of informants in this study amounted to six people who were representative and met the criteria in this assessment. Data analysis techniques in this study used data collection, data condensation, data presentation, and drawing conclusion/verification. The results of this study indicate that the factors that influence the decision to purchase thrift online store goods are affordable prices among students and in accordance with the quality of the products obtained, very diverse products depending on the marketer, easy and efficient distribution access but on the other hand sometimes vulnerable experience fraud because of the difficulty of getting trusted marketers, various promotions and attracting consumers' attention depending on the creativity of each marketer. The purchase decisiom is stated to be satisfied and will make a repeat purchase if the product quality and price are in accordance with what is expected.